2023
DOI: 10.1038/s41467-023-38597-0
|View full text |Cite
|
Sign up to set email alerts
|

An injectable liposome-anchored teriparatide incorporated gallic acid-grafted gelatin hydrogel for osteoarthritis treatment

Abstract: Intra-articular injection of therapeutics is an effective strategy for treating osteoarthritis (OA), but it is hindered by rapid drug diffusion, thereby necessitating high-frequency injections. Hence, the development of a biofunctional hydrogel for improved delivery is required. In this study, we introduce a liposome-anchored teriparatide (PTH (1–34)) incorporated into a gallic acid-grafted gelatin injectable hydrogel (GLP hydrogel). We show that the GLP hydrogel can form in situ and without affecting knee mot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The blue dye selectively binds to glycosaminoglycans in the cartilage, resulting in distinct and intense coloration in specific regions. 54 At 8 weeks postsurgery, TB staining revealed that the LZIF-8/WMg-MOF@GEL group exhibited a more pronounced staining area compared to the other control group, showing statistical differences (Figure 7C). The results presented above indicate that LZIF-8/WMg-MOF@GEL possesses superior cartilage regeneration and promotes tendon repair capabilities.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The blue dye selectively binds to glycosaminoglycans in the cartilage, resulting in distinct and intense coloration in specific regions. 54 At 8 weeks postsurgery, TB staining revealed that the LZIF-8/WMg-MOF@GEL group exhibited a more pronounced staining area compared to the other control group, showing statistical differences (Figure 7C). The results presented above indicate that LZIF-8/WMg-MOF@GEL possesses superior cartilage regeneration and promotes tendon repair capabilities.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Toluidine blue (TB) staining is employed to detect the content and distribution of fibrous cartilage. The blue dye selectively binds to glycosaminoglycans in the cartilage, resulting in distinct and intense coloration in specific regions . At 8 weeks postsurgery, TB staining revealed that the LZIF-8/WMg-MOF@GEL group exhibited a more pronounced staining area compared to the other control group, showing statistical differences (Figure C).…”
Section: Resultsmentioning
confidence: 92%
“…In the OA environment, GGA hydrogels can enhance the expression of SOX9 (which represents the secretion of the articular cartilage ECM) and Bcl-2 (an antiapoptotic protein) while reducing the expression of BAX (a proapoptotic protein) and the protein MMP13 (a joint-disrupting factor in OA). 152 These findings indicate that the GGA hydrogel, which contains GA, has potential application value in the treatment of OA.…”
Section: Biomedical Applicationsmentioning
confidence: 82%
“…For example, Li et al designed a novel injectable enzyme-initiated gelation hydrogel (GGA@Lipo@PTH (1–34), GLP) that could gel in situ rapidly in the presence of transglutaminase (TG) after intra-articular injection, regulate cartilage metabolism through the sustained release of teriparatide (PTH (1–34)) and finally alleviate osteoarthritis. 224 They first obtained a gelatin derivative (GGA) which was grafted with gallic acid via the crosslinking of the carboxyl groups in gallic acid and the amino groups in gelatin. Then, liposomes encapsulating PTH (1–34) in the core were incorporated into the GGA solution to obtain the pre-gel of GLP.…”
Section: Fabrication Of Injectable Hydrogelsmentioning
confidence: 99%